2010
DOI: 10.1371/journal.pone.0009792
|View full text |Cite
|
Sign up to set email alerts
|

Identification of gp96 as a Novel Target for Treatment of Autoimmune Disease in Mice

Abstract: Heat shock proteins have been implicated as endogenous activators for dendritic cells (DCs). Chronic expression of heat shock protein gp96 on cell surfaces induces significant DC activations and systemic lupus erythematosus (SLE)-like phenotypes in mice. However, its potential as a therapeutic target against SLE remains to be evaluated. In this work, we conducted chemical approach to determine whether SLE-like phenotypes can be compromised by controlling surface translocation of gp96. From screening of chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 43 publications
3
45
1
Order By: Relevance
“…Recently, T cells from mice treated with an HSP90 inhibitor showed reduced responsiveness to activating antigens in the collagen induced arthritis model. 25 Han et al 11 found that an inhibitor for the endoplasmic reticulum homologue of HSP90, gp96, reduced both the CD4 1 memory T cells and activated CD4 1 T cells in the spleen and lymph nodes. The effects of HSP90 inhibition on T-cell populations might be The effect of heat shock protein 90 inhibition in lupus mice SK Shimp III et al 263 explained by the fact that stimulation of the T-cell receptor leading to T-cell activation requires HSP90 to stabilize lymphocyte-specific protein tyrosine kinase (Lck) in order to initiate activation.…”
Section: Mature B Cells Were Decreased In Mice Treated With 17-dmagmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, T cells from mice treated with an HSP90 inhibitor showed reduced responsiveness to activating antigens in the collagen induced arthritis model. 25 Han et al 11 found that an inhibitor for the endoplasmic reticulum homologue of HSP90, gp96, reduced both the CD4 1 memory T cells and activated CD4 1 T cells in the spleen and lymph nodes. The effects of HSP90 inhibition on T-cell populations might be The effect of heat shock protein 90 inhibition in lupus mice SK Shimp III et al 263 explained by the fact that stimulation of the T-cell receptor leading to T-cell activation requires HSP90 to stabilize lymphocyte-specific protein tyrosine kinase (Lck) in order to initiate activation.…”
Section: Mature B Cells Were Decreased In Mice Treated With 17-dmagmentioning
confidence: 99%
“…61 The inhibitor for gp96 was shown to reduce populations of mature B cells, B2201 and MHC class II1 cells. 11 However, it has also been shown that splenic plasma cells and germinal center B cells are unaffected by 17-DMAG treatment. 91 We found that only follicular B cells were affected by the HSP90 inhibition treatment, while marginal zone B cells (B1a and B1b) were not significantly affected.…”
Section: Mature B Cells Were Decreased In Mice Treated With 17-dmagmentioning
confidence: 99%
See 2 more Smart Citations
“…Pharmacological inhibition of Hsp90 function has therefore emerged as a promising method to ameliorate inflammatory cascades, as it has been demonstrated in various experimental mouse models of autoimmune diseases, including autoimmune encephalomyelitis (Dello Russo et al 2006), rheumatoid arthritis (Rice et al 2008;Yun et al 2011), and systemic lupus erythematosus (Han et al 2010;Shimp et al 2012a). Our own recent research work showed that, by downregulating T cell responses, this kind of treatment is also effective in mice with the experimentally induced subepidermal autoimmune blistering skin disease epidermolysis bullosa acquisita (Kasperkiewicz et al 2011).…”
Section: Introductionmentioning
confidence: 99%